قواعد النحو وأثرها في تعليم اللغة العربية في إندونيسيا - Qareebullah Babkr Musthofa (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2018)
This Article contains of four topics: 1) the beginning of the spread of Arabic language, 2) the status of Arabic language teaching in Indonesia 3 ) the problems in Arabic language teaching, and 4) the appropriate solutions for teaching Arabic. The spread of the Arabic language began in Indonesia with the entry of Islam in the first century, in addition to the teaching of the Holy Quran and Islamic values, and then all the purposes. The method of teaching Arabic language has passed through stages beginning with the teaching of the language verbally and ending with teaching it for special and professional purposes. The most important problems of education are the formulation of objectives, subjects, teaching, and methods. The most important solutions to these problems are the formulation of objectives that are compatible with the spirit of the times, the development of appropriate subjects for the Arabic language learner, and the choice of the appropriate method for communicating the Arabic language.